PERANCANGAN STREAMER DILENGKAPI DENGAN SIKLUS BOILER OTOMATIS SEBAGAI ALAT STERILISASI BAGLOG SEBAGAI MEDIA TANAM - Indah Pratiwi (LPPM Universitas Abdurrab, 2026)
Energy demand in Indonesia's industrial sector continues to rise, particularly within oyster mushroom cultivation, which relies on LPG for baglog sterilization. However, this process is often inefficient, resulting in high fuel consumption and diminished mushroom yields. This study aims to analyze the influence of retention time and steam flow rate variations on thermal efficiency, specific fuel consumption, and sterilization effectiveness of an LPG-fueled baglog steamer. The research was conducted at the Chemical Engineering Laboratory, Sriwijaya State Polytechnic, from April to December 2025. The methodology involved preparing baglogs using wood sawdust, bran, corn flour, and lime, followed by the sterilization of 12 units. Experimental variables included retention times ranging from 2 to 6 hours (with a constant flow rate of 3.04 kg/h) and flow rates ranging from 2.79 to 3.25 kg/h (with a constant retention time of 4 hours). Observations encompassed temperature, pressure, and LPG consumption measurements, alongside sterilization verification through inoculation, incubation, and organoleptic examination. Results indicated a peak thermal efficiency of 58.34% at a retention time of 4 hours. The lowest specific fuel consumption was observed at longer retention times, while sterilization effectiveness reached 91.7%, yielding a total mushroom mass of 4,829 grams at 6 hours. It is concluded that the optimal operating condition is a retention time of 4 hours with a flow rate of 3.04 kg/h to achieve a balance between efficiency and effectiveness. Recommendations include the addition of thermal insulation to the steamer to minimize heat loss and enhance energy efficiency.